Effect of wobbling mass modeling on joint dynamics during human movements with impacts - Bélaise, Colombe; Blache, Yoann; Thouzé, Arsène; Monnet, Tony; Begon, Mickaël (Multibody system dynamics, 2016)
The effect of wobbling mass modeling on joint efforts estimation has mainly been assessed using computer simulation. The main challenge of an experimental approach for calculating joint efforts is to distinguish bone to wobbling mass inertial parameters and kinematics. Our objective was to experimentally assess the wobbling mass effect on jump dynamics. Eleven healthy men performed hopping and landing tasks on a force platform. Eighty-five skin markers were stuck on the subjects’ left lower-limbs to estimate joint kinematics. Two multibody dynamic models with (MM: mobile model) or without (RM: rigid model) the wobbling mass displacement (6 degrees of freedom) with respect to the underlying bones were proposed. Inertial parameters for bones and wobbling masses were calculated separately, based on an original approach that combines geometric anthropometric data and predictive equations. After calculating joint efforts using inverse dynamics, the effect of the model (MM vs. RM) on the peak efforts at hip and knee joints was determined using ANOVAs with repeated measures. The main finding was that the RM model significantly underestimated the hip flexion-extension and axial rotation peak torques for the hopping task. For the landing task, wobbling mass modeling had no influence on the peak joint efforts, contrary to previous simulation-based findings. This finding may have resulted from a large inter-subject variability observed in the wobbling mass effect on the peak joint values. This study corroborates that wobbling mass modeling may have an impact on evaluating the risk of musculoskeletal injuries.